Development Of Digital-Based Classroom Learning E-Learning Web Interface Study Bumigora University Project Case - Widia Febriana; Rini Anggraini; Irwan Cahyadi; I Nyoman Yoga Sumadewa (Sumber Belajar Sejahtera, 2023)
Bumigora University has been trusted as a campus that can develop interactive learning models based on free open source software for all teaching and learning activities related to computers at Bumigora University. One of the obstacles that arises is doing full-day learning (8 hours) there is limited time and the material load is quite dense so a breakthrough learning model is needed that gives rise to acceleration and ease of transferring knowledge from learning sources (lecturers, textbooks, and other learning resources) to student. Therefore, Bumigora University designed an application in the form of a website where in this application admins and teachers can carry out management processes on student data and can convey information and materials or assignments to students. Students can see information about teaching and learning activities and can see subjects, materials, and grades. You can also download materials. From the results of testing using the Black Box Testing method that has been carried out, it can be concluded that the Bumigora University E-Learning System has fulfilled the research objectives to be used properly, as evidenced by the functioning of the functions in the application properly.